Aplikasi Detasseling Dan Mol Buah-Buahan Pada Sistem Tanam Jajar Legowo Tanaman Jagung (Zea mays L.) - Ella Jumhariati; Wiwik Hardaningsih (GEMA AGRO, 2022)
One of the basic needs of people i Indonesia is corn. Corn is one of the most important food crops after rice and wheat. Apart from being a human food ingredient (a sourdc of carohydrates), corn is also used as anumal feed and also as an industrial raw materil. The need for corn for animal feed continuesin to increase every yera. This is in line with the developmentof the livestoc industry, especially in the Lima Puluh Kota regency. Some factors that cause the potential for corn production are lessthan the maximum are the presenceof pests that result in decreased production and the influence of weather that can inhibit corn growth. Suboptimal maintenance in the cultivation process can also reduce corn production, so it needs good maintenance. There fore it is necessary to develop this cultivation of maize with the aim to determine the increase in crop production by applying the detasseling and fruit mole in the legowo row planting system and see the feasibilityof the corn cultivation business with detasseling technology and fruit moles in the legowo row planting system. This busiess with detasseling technology and fruit mole in the legowo row row planting system andseed the feasibility of the corn cultivation business with detasseling technology and fruit molei in the legowo rw planting system. This business devolopment is carried out in the payakumbuh state agricultural polytechnic experimental field in february to june with with a land area of 250 m2, which is 125 m2 with detasseling technology and 125 m2 without detasseling. Which is very real with respect to the number of rows/cob, number of seed/row, and weight of 100 seeds. Corn production obtained by detasseling treatment was 113 kg and without treatment was 95 kg.